2020
DOI: 10.1186/s40834-020-00123-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of emergency contraceptive practice among female university students in Ethiopia: systematic review and meta-analysis

Abstract: Introduction Despite Ethiopia’s government’s commitment to alleviating unwanted pregnancy and unsafe abortion by increasing holistic reproductive health service accessibility, the rate of unwanted pregnancy among female students in the universities is distressing and becoming a multisectoral concern. Therefore, this systematic review aimed to assess the prevalence and determinant of emergency contraceptive practice among female university students in Ethiopia. Result The overall pooled prevalence of emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…Nearly one-third of students in our study (29%) reported being sexually active, and contraceptive users overwhelmingly used shortacting methods, including emergency contraception, condoms, and oral contraceptive pills, likely due to limited choice of contraceptive methods on campuses. These findings are similar to prior research in Ethiopia; a study among female students at Wolaita Sodo University found that 24% were sexually active (34), while a meta-analysis of studies on emergency contraceptive use among female university students in Ethiopia identified a pooled prevalence of 34.5% (35). Approximately one-fifth of respondents in our study reported ever experiencing an unwanted pregnancy, and 14% reported having had an abortion.…”
Section: Discussionsupporting
confidence: 88%
“…Nearly one-third of students in our study (29%) reported being sexually active, and contraceptive users overwhelmingly used shortacting methods, including emergency contraception, condoms, and oral contraceptive pills, likely due to limited choice of contraceptive methods on campuses. These findings are similar to prior research in Ethiopia; a study among female students at Wolaita Sodo University found that 24% were sexually active (34), while a meta-analysis of studies on emergency contraceptive use among female university students in Ethiopia identified a pooled prevalence of 34.5% (35). Approximately one-fifth of respondents in our study reported ever experiencing an unwanted pregnancy, and 14% reported having had an abortion.…”
Section: Discussionsupporting
confidence: 88%
“…13 It is consistent with results from a South African 11 Rate of sexually active women, accessibility of information on contraception, sexual and reproductive health education, socio-cultural differences and level of urbanizations of the study areas might be accountable for the discrepancy. 10,15,22 According to this study, ECP was utilized by the majority (61.8%) of female undergraduates who had history of sexual intercourse. This figure is higher than previous reports from different universities of African countries such as South Africa (21.2%), Kenya (20%), Nigeria (15.2%) and Rwanda (5%).…”
Section: Discussionmentioning
confidence: 91%
“… 11 Rate of sexually active women, accessibility of information on contraception, sexual and reproductive health education, socio-cultural differences and level of urbanizations of the study areas might be accountable for the discrepancy. 10 , 15 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations